DAMPAK SARS-COV-2 TERHADAP SAHAM PERUSAHAAN SUB SEKTOR PERHOTELAN, RESTORAN DAN PARIWISATA DI BURSA EFEK INDONESIA UNTUK PERIODE BERAKHIR BULAN SEPTEMBER 2020 - Via Krismawati; Maslichah Maslichah; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The SARS-CoV-2 incident is one of the causes which able to affect capital market investment activities in Indonesia. This study aims to know the SARS-CoV-2 incident impact on the shares of hospitality industry, restaurant, and tourism subsector The population of this research is hospitality industry, restaurant, and tourism subsector on the BEI. The sampling technique used purposive sampling. The data was taken in the form of secondary data with documentation method. This kind of research used an event study with an event window during t-7 (before the event) and t + 7 (at the time of the event). The data used is data in the form of monthly share prices. Then the data were analyzed using paired t test. The results prove that average abnormal return with a value (0.049 <0.05) there is a difference between before and during the SARS-CoV-2 incident. Meanwhile, average trading volume activity with a value (0.293> 0.05) proved that there was no difference between before and during the SARS-CoV-2 incident.Keywords: SARS-CoV-2, Average Abnormal Return, and Average Trading Volume Activity.